Pengaruh Penambahan Tangki Pengumpul Kondensat Terhadap Penghematan Energi Boiler Cochran pada PT. Eastern Pearl Flour Mills - Juhamri, Juhamri; Astuty, Sri; Subur, Hikmayani (Jurnal Teknik Mesin, 2024)
One effort for saving the energy in the production process is the reuse wasted energy from these productions. This study aimed (1) to determine the effectiveness of the addition of the condensate steam collector tank collection tank on the return pipe line of the boiler on the saving capacity of the Cochran boiler, which was determined based on the boiler efficiency, the fuel consumption, and the amount of water impurity (TDS);(2). to determine the balance between the mass system and the energy boiler system as one of the effectiveness evaluation system of the additionall condensate collector tank. This research was conducted at PT. Eastern Pearl Foulr Mills, Makassar – more specifically at the boiler section and power station. The method used was that the data were collected and processed before and after the condensate collector tank was installed. Thus, it was expected that the difference showing the effect of the additional tank on the energy saving of boiler system. Besides, the research would also determine the conditions of each line point of the working fluid path; next, the efficiency of the boiler, the consumption of the fuel and the amount of the water impurity in the fluid working path would be determined; finally, the mass and the energy balance of the existing system would be determined. The research result revealed that efficiency before the installation was 52.72 % in average, and after the installation was 64.55 % in average. Before the installation of the condensate collector tank, the average fuel consumption was 94.39 kg/hour, while after the installation the average fuel consumption was 75.45 kg/hour. The reason was that the water used tended to be cleaner as seen in the lower TDS than before the installation. Then, the fuel energy of 849. 45 kW was able to produce useful steam energy of 556. 94 kW.